Experimental Measurement of Arc Motion and Light Flicker Frequencies in the HID Lamps - Amer Lakhdar; Hamouda Messaoud; Benachiba Chellali; Marcus Wolff (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
In order to reduce the electric consumption for high intensity discharge lamps, the use of high frequencies electronic ballasts represents both a solution and many advantages such as the decrease in the congestion and low costs. However, high frequency operation is not regarded as perfectly reliable due to the appearance of acoustic resonances inside the arc tube, which can result in low frequency light flicker and even lamp destruction. Here we experimentally determined light flicker frequencies using a photodiode which detects the light intensity fluctuation for a high intensity discharge lamp of 50W. Additionally, the arc motion frequencies are determined with the aid of a camera. The results obtained are compared with those of a lamp of the same type but with different power (35W).